2021
DOI: 10.33889/ijmems.2021.6.2.033
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization and Maximum Entropy Results for MX/G/1 Retrial G-Queue with Delayed Repair

Abstract: This paper examines an MX/G/1 retrial model with negative customers including the concepts of working vacation, Bernoulli feedback, delayed repair, state-dependent and multi-optional services. Such a queue is quite relevant in real world, for instance in computer systems, manufacturing organisations, packet-switching networks, telecommunication systems, etc. The arrival pattern of customers is according to Poisson distribution. The service is such that first essential service (FES) is provided to every custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…which is the obtained Shannonian formalism in [20]. This shows the strength of the newly devised KLD formalism.…”
Section: Proofsupporting
confidence: 69%
See 2 more Smart Citations
“…which is the obtained Shannonian formalism in [20]. This shows the strength of the newly devised KLD formalism.…”
Section: Proofsupporting
confidence: 69%
“…It is observed that as 𝑞(0) → 1 , τ → τ , which reduces to the Shannonian limiting case obtained (c,f., [20]). Corollary 1.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…When there were obstacles on the optimal path, they sought a new path through a turning point setting to reduce the system resources consumed by the algorithm. As the demand for robot intelligence increases, the environment it faces becomes more and more complex, and the focus of path planning research gradually turns to application research in the complex dynamic environment [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The optimization design of electrical products is a skill with great theoretical and technical difficulties. The design of electrical products requires a full combination of advanced theoretical knowledge in the field and the expertise of outstanding scholars [12][13]. At the same time, the above work will be completed, excellent electrical products will be designed.…”
Section: Figure 2 Exploration Of Online and Off Line Experiential Tea...mentioning
confidence: 99%